Pengembangan Model Pendidikan Karakter Bangsa Berparadigma Islami di Sekolah Menengah Atas Muhammadiyah Bangkinang - Azwir Salam (Journal on Education, 2023)
The social and cultural condition of society these days is threatened because it is facing a crisis of positive behavior which shows that education has not been able to build national character. SMA Muhammadiyah Bangkinang shows the values of politeness, Islamic character, and school culture so that it is necessary to design a national character education model with an Islamic paradigm. The purpose of this study was to produce a model of national character education with an Islamic paradigm at Bangkinang Muhammadiyah High School. The research method is development using the Borg and Gall design. The research subjects were school principals, teaching staff, and the school environment. The research object is the development of an Islamic paradigm character education model at Bangkinang Muhammadiyah High School. Data collection techniques are observation, documentation, and interviews. Data were analyzed using proportions and then interpreted. This research produced a model of national character education with an Islamic paradigm at Bangkinang Muhammadiyah High School which was obtained by restructuring the implementation of character values in the school environment and the Islamic character values of the Muhammadiyah Association. The implementation of Islamic character values in learning and in the school environment is in the Cultured Already category.